A verified proof checker for higher-order logic - Abrahamsson, Oskar (Journal of logical and algebraic methods in programming, 2020)
We present a computer program for checking proofs in higher-order logic (HOL) that is verified to accept only valid proofs. The proof checker is defined as functions in HOL and synthesized to CakeML code, and uses the Candle theorem prover kernel to check logical inferences. The checker reads proofs in the OpenTheory article format, which means proofs produced by various HOL proof assistants are supported. The proof checker is implemented and verified using the HOL4 theorem prover, and comes with a proof of soundness.